2016
DOI: 10.1057/jphp.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Eviction and loss of income assistance among street-involved youth in Canada

Abstract: Loss of housing and income assistance among vulnerable youth has not been well described in the literature, yet it is a crucial issue for public health. This study examines the prevalence and correlates of loss of income assistance as well as eviction among street-involved youth. We collected data from a prospective cohort of street-involved youth aged 14–26. Among 770 participants, 64.3% reported having housing and 77.1% reported receiving income assistance at some point during the study period. Further, 28.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
(39 reference statements)
0
21
0
Order By: Relevance
“…alcohol consumption, gambling and drug use) was an independent risk factor for eviction (OR = 8.0, 95% CI = 1.56–4.24), specifically, drug addiction was significantly more frequent among those who were evicted compared to those who were not evicted (Van Laere et al., ). Analysis of data from the At‐Risk Youth Study in Canada also found that heavy alcohol use was associated with evictions (Zivanovic et al., ) even after controlling for other confounding factors.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…alcohol consumption, gambling and drug use) was an independent risk factor for eviction (OR = 8.0, 95% CI = 1.56–4.24), specifically, drug addiction was significantly more frequent among those who were evicted compared to those who were not evicted (Van Laere et al., ). Analysis of data from the At‐Risk Youth Study in Canada also found that heavy alcohol use was associated with evictions (Zivanovic et al., ) even after controlling for other confounding factors.…”
Section: Resultsmentioning
confidence: 98%
“…Desmond, An, Winkler, & Ferriss, (Desmond et al., ) also conducted a particularly notable study combining survey and court data for a sizable sample. Other studies reported on prospective cohorts but the temporal relation between variables could not be determined and analyses were based on associations using time‐varying variables (Kennedy et al., ; Zivanovic et al., ). Overall, review of all ten studies revealed the most salient factors related to risk of evictions could be grouped into four categories, by order of the strength of their association reported in the literature: financial hardship (60% of studies), sociodemographic and household characteristics (40% of studies); substance use (40% of studies); and other health problems such as physical and mental conditions (80% of studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Canada, street-involved youth are a highly marginalized population that often experience reduced access to healthcare, and are more likely to become involved with the criminal justice system and exposed to food insecurity, homelessness and unstable housing, as well as limited job and education opportunities (Tyler & Johnson, 2006; Worthington et al, 2008; Zivanovic et al, 2016). Studies have shown that up to 95% of street-involved youth have ever used illicit drugs whereas over 40% have ever injected drugs (Barnaby, Penn, & Erickson, 2010; Canada, 2007; Kerr et al, 2009; Public Health Agency of Canada, 2006; Worthington et al, 2008).…”
Section: Introductionmentioning
confidence: 99%